Ecofeminism - Mies, Maria (Fernwood, 1993)
Maria mies and vandana shiva, internationally respected feminist activists and writers, come together in this book on a controversial environmental agenda using interview material, they bring together womens perspectives from north and south on environmental deterioration and develop a new way of approaching this body of knowledge, which is at once practical and philosophical? do women involved in environmental movements see a link between patriarchy and ecological degradation? what are the links between global militarism and the destruction of nature? in exploring such questions, the authors criticize prevailing theories and develop an intellectually rigorous ecofeminist perspective rooted in the needs of everyday life they argue for the acceptance of limits, the rejection of the commoditization of needs, and a commitment to a new ethics about the author maria mies is a sociologist and author of several books including indian women and patriarchy, patriarchy and accumulation on a world scale, the lace makers of narsapur and, with claudia von werlhof and veronika bennholdt-thomsen, women: the last colony as well as articles in numerous journals after returning from many years in india, she became head of the womens studies programme at the institute of social studies in the hague, and subsequently professor of sociology at the fachhochsch?le in cologne she is now active in womens and environmental movements in germany? vandana shiva ? physicist, philosopher and feminist activist ? is director of the research foundation for science, technology and natural resource policy, dehradun, india she has been active in citizens action against environmental destruction, including the chipko movement, and is highly critical of current agricultural and reproductive technologies she is the author of hugely successful staying alive: women, ecology and developme